Pengaruh Struktur Modal Terhadap Profitabilitas Perusahaan (Studi Pada Perusahaan Manfaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2020 - 2024): (Studi Pada Perusahaan Manfaktur Sub Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2020 - 2024) - Mutiara Sari Ramadani; Agung Widhi Kurniawan; Nurman Nurman; Anwar Ramli; Muhammad Ichwan Musa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study aims to analyze the effect of capital structure on the profitability of food and beverage subsector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The main focus of this research is to determine the extent to which the composition of company financing through debt and equity (Debt to Equity Ratio) influences the company’s ability to generate net income (Return on Equity). This research uses a quantitative approach with a descriptive method and simple linear regression analysis. The data used are secondary data obtained from the annual financial reports of ten food and beverage subsector companies listed on the IDX for the 2020–2024 period. The independent variable in this study is capital structure, proxied by the Debt to Equity Ratio (DER), while the dependent variable is profitability, proxied by the Return on Equity (ROE). Data analysis was conducted using the SPSS software to test the relationship and effect between the two variables.The results indicate that the capital structure, as measured by the Debt to Equity Ratio (DER), has a significant effect on profitability, as measured by the Return on Equity (ROE). This finding suggests that proportional use of debt can provide a positive leverage effect on profitability, while excessive debt levels may reduce profits due to increased interest expenses. Overall, the study confirms that maintaining an optimal capital structure is crucial for sustaining the financial performance of food and beverage manufacturing companies in Indonesia.